Odpowiedź :
P=1/2a*h
P=1/2*(4n-4)*(4n-11)
P=(2n-2)*(4n-11)
P=8n²-22n-8n+22
P=8n²-30n+44
P=1/2*(4n-4)*(4n-11)
P=(2n-2)*(4n-11)
P=8n²-22n-8n+22
P=8n²-30n+44
P= 1/2 a * h
P= 1/2 * (4n-4) * (4n-11)
P= 16n² - 44 n + 16 n - 44 (całość przez 2 w mianowniku)
P = 16n² - 28n - 44 (całość przez 2 w mianowniku )
P= 1/2 * (4n-4) * (4n-11)
P= 16n² - 44 n + 16 n - 44 (całość przez 2 w mianowniku)
P = 16n² - 28n - 44 (całość przez 2 w mianowniku )
Wybierasz dwie przyprostokątne- najkrótsze, jedna z nich będzie wysokością:
P= 1/2 * (4n-4) * (4n-11)
P= 16n² - 44 n + 16 n - 44
P = 16n² - 28n - 44
P= 1/2 * (4n-4) * (4n-11)
P= 16n² - 44 n + 16 n - 44
P = 16n² - 28n - 44